Comprehensive analysis of TP53 and SPOP mutations and their impact on survival in metastatic prostate cancer - Zhou, Jie; Lai, Yiming; Peng, Shengmeng; Tang, Chen; Chen, Yongming; Li, Lingfeng; Huang, Hai; Guo, Zhenghui (Frontiers in Oncology, 2022)
Abstract Background: Although TP53 and SPOP are frequently mutated in metastatic prostate cancer (PCa), their prognostic value is ambiguous, and large sample studies are lacking, especially when they co-occur with other genetic alterations. Methods: Genomic data and patients’ clinical characteristics in PCa were downloaded from the cBioPortal database. We extensively analyzed other gene alterations in different mutation status of TP53 and SPOP. We further subdivided TP53 and SPOP mutation into subgroups based on different mutation status, and then evaluated the prognostic value. Two classification systems for TP53 survival analysis were used. Results: A total of 2,172 patients with PCa were analyzed in our study, of which 1,799 were metastatic PCa patients. The mutual exclusivity analysis showed that TP53 and SPOP mutation has a strong mutual exclusion (p＜0.001). In multivariable analysis, truncating TP53 mutations (HR=1.764, 95%CI:1.396-2.230, p<0.001) and other TP53 mutations(HR=1.553, 95%CI:1.266-1.904, p<0.001) were independent negative prognostic markers in metastatic PCa, whereas SPOP mutations(HR=0.580, 95%CI:0.419-0.803, p<0.001) were an independent prognostic factor for better prognosis. Mutations in TP53 were significantly associated with wild-type status for SPOP and CDK12, structural variants/fusions for TMPRSS2 and ERG, AR amplification and PTEN deletion (p＜0.001). And truncating TP53 mutations have higher AR amplification rates than other TP53 mutations (p=0.022). Consistently, truncating TP53 mutations had a worse prognosis than other TP53 mutations (p<0.05). Then Kaplan-Meier survival curve showed that Co-occurring TP53 mutations in AR amplification or PTEN deletion tumors significantly reduced survival (p<0.05). Furthermore, those with SPOP-mutant tumors with co-occurring TP53 truncating mutations had shorter overall survival than those with SPOP-mutant tumors with wild-type or other TP53 mutations. Conclusions: This study found that TP53 and SPOP mutations were mutually exclusive and both were independent prognostic markers for metastatic PCa. Genomic alteration and survival analysis revealed that TP53 and SPOP mutations represented distinct molecular subtypes. Our data suggest that molecular stratification on the basis of TP53 and SPOP mutation status should be implemented for metastatic PCa to optimize and modify clinical decision-making.